OBSERVATIONAL STUDY REGARDING SOMATICAL DEVELOPMENT FOR THE MIRON COSTIN SECONDARY SCHOOL SUCEAVA 12 YEARS OLD STUDENTS - Petrariu Ileana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
This scientific work was conducted in order to present details regarding the somatic development level of the 12-year-old students at the Miron Costin Secondary School in Suceava. In this study, a total of 100 students were tested: 42 girls and 58 boys. They have been subjected to a series of tests to assess the level of somatic development (height, body mass, arm span, BMI).